Three in the Game, the Fourth Forgotten - Novkov, Mitko (Acta Nova Humanistica: A Journal of Humanities Published by New Bulgarian University, 2025)
The focus of the article “Three in the Game, the Fourth Forgotten” is the incomplete research of the notable Bulgarian literary critic, translator and essayist Tzvetan Stoyanov’s The Genius and His Mentor (1978). Tzvetan Stoyanov’s book examines the relationship between the great Russian writer Fyodor Mikhailovich Dostoevsky and the Chief Prosecutor of the Russian Holy Synod Konstantin Petrovich Pobedonostsev, the tutor of Emperor Alexander III, considered one of the most retrograde and reactionary thinkers and public figures in general in all of Russian history. The questions that the article asks are: 1) why did Konstantin Pobedonostsev turn specifically to Fyodor Dostoevsky with the desire to turn him into a spokesman for the conservative wing of Russian humanitarian thought in the 19th century, even though there were other significant figures of that time who could have fulfilled the same role?; 2) why does Tzvetan Stoyanov emphasize Dostoevsky’s ties with Pobedonostsev without taking into account the above-mentioned fact?; 3) did Dostoevsky really protect himself from Pobedonostsev’s influence and not allow him to fulfill his intentions towards him? The conclusion drawn by the article is that Dostoevsky and Pobedonostsev were not such antagonists as Tzvetan Stoyanov presents them, but rather like-minded people, and only death prevented Dostoevsky from finally transferring to Pobedonostsev’s camp.